Pemanfaatan Serai untuk Teh Herbal sebagai Upaya Pemberdayaan Ekonomi Petani Serai di Desa Wonosari, Kecamatan Ngombol, Kabupaten Purworejo - Shafira Maharani; Nofita Eka Saputri; Nesya Tisna Putri; Fia Eviana; Susi Widjajani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Purworejo Regency is one of the centers of herbal plant production in Indonesia. One of these is lemongrass, which is widely found in the Ngombol area. Furthermore, this plant can be used to make herbal products. However, the selling value of this plant is still relatively low because it relies solely on middlemen or collectors. One product made from lemongrass is essential oil. The goal of this Community Service program is to increase the selling value of lemongrass and provide new business opportunities to increase the income of local farmers, especially Mrs. Kasminah in Wonosari Village, Ngombol District, Purworejo Regency. The implementation method includes preparation, core, and completion. The result of this activity is the creation of a new innovation in the form of a practical herbal drink without preservatives that has quite good market potential and is in demand by consumers. Then, the product is branded Sempontea. Achievements during the activity include a significant increase in income, as well as the creation of effective offline and online marketing strategies. This activity also succeeded in establishing a sustainable business ecosystem and increasing environmental awareness through the use of herbal plants. Overall, this community service activity has succeeded in increasing the selling value of lemongrass plants, improving the economy of local farmers, and providing social and economic impacts for the community through the utilization of local resources.